Agitation and Dementia: Prevention and Treatment Strategies in Acute and Chronic Conditions - Carrarini, Claudia; Russo, Mirella; Dono, Fedele; Barbone, Filomena; Rispoli, Marianna G.; Ferri, Laura; Di Pietro, Martina; Digiovanni, Anna; Ajdinaj, Paola; Speranza, Rino; Granzotto, Alberto; Frazzini, Valerio; et al. (Frontiers in Neurology, 2021)
Agitation is a behavioral syndrome characterized by increased, often undirected, motor activity, restlessness, aggressiveness, and emotional distress. According to several observations, agitation prevalence ranges from 30 to 50% in Alzheimer's Disease, 30% in Dementia with Lewy bodies, 40% in Frontotemporal Dementia, and 40% in Vascular Dementia (VaD). With an overall prevalence of about 30%, agitation is the third most common neuropsychiatric symptom (NPS) in dementia, after apathy and depression, and it is even more frequent (80%) in residents of nursing homes. The pathophysiological mechanism underlying agitation is represented by a frontal lobe dysfunction, mostly involving the anterior cingulate cortex (ACC) and the orbitofrontal cortex (OFC), respectively meaningful in selecting the salient stimuli and subsequent decision-making and behavioral reactions. Also, increased sensitivity to noradrenergic signaling has been observed, possibly due to a frontal lobe up-regulation of adrenergic receptors, as a reaction to the depletion of noradrenergic neurons within the locus coeruleus (LC). Indeed, LC neurons mainly project towards OFC and ACC. These observations may explain the abnormal reactivity to weak stimuli and the global arousal found in many patients who have dementia. Furthermore, agitation can be precipitated by several factors, e.g., the sunset or low lighted environments as in the sundown syndrome, hospitalization, or the admission to nursing residencies, or changes in pharmacological regimens. In recent days, the global pandemic has increased agitation incidence among dementia patients and generated higher distress levels in patients and caregivers. Hence, given the increasing presence of this condition and its related burden on society and the health system, the present point of view aims at providing an extensive guide to facilitate the identification, prevention, and management of acute and chronic agitation in dementia patients.